Malaysian Facebook Users Online Airline Tickets Purchase Intention: Antecedents and Outcome of eWOM - Janifer, Lunyai; Goh, Yen Nee; Zurina, Mohaidin; Mohd Waliuddin, Mohd Razali (Human Resource Management Academic Research Society, 2021)
This study aims to identify the antecedents of eWOM in the context of online airline ticket purchase intention by Malaysian consumers. Additionally, this study also seeks to examine the relationship between eWOM and purchase intention. The research model was examined by employing survey questionnaire method obtained from 530 Malaysian consumers through mall-intercept method and data was analyzed using PLS. The findings revealed that information usefulness, source credibility, information accuracy, and information timeliness have a positive and significant relationship with eWOM and involvement moderates the relationships between eWOM and purchase intention. Despite the fact that this study is limited to eWOM in the context of online airline tickets purchasing of Malaysian Facebook users, it is expected to be of value to airline and travel organizations in Malaysia. This study extends the applicability of S-O-R Model and ELM Model to the eWOM domain in the context of social media, with an approach to investigate consumer’s purchase intention.